The Influence of Entrepreneurial Mindset and Creativity on Entrepreneurial Intention : A Study on Retired Employees of Great Giant Foods - Zita Iztihari; Rr. Erlina (Harmony Management: International Journal of Management Science and Business, 2025)
This research examines how entrepreneurial mentality and inventiveness affect retired PT Great Giant Foods (GGF) Lampung Tengah workers' entrepreneurial intention. The quantitative study included questionnaires from 120 participants. The assumptions were tested using multiple linear regression with partial testing (t-test). The findings corroborate H1, demonstrating that entrepreneurial attitude positively and significantly affects entrepreneurial ambition. The more entrepreneurial a retiree is, the more likely they are to establish and maintain a firm. Creativity also positively and significantly affects entrepreneurial ambition, supporting H2. Thus, retiree inventiveness boosts entrepreneurial ambition. The lowest average score in the entrepreneurial mentality characteristic, activity planning, requires particular attention. This measure helps retirees arrange their business activities more consistently and systematically. Enhancing creativity and ideation is essential for company innovation. Improvements in these factors should boost retirees' entrepreneurial intent and success.